Vaheesan, Sandeep. Democracy in Power: A History of Electrification in the United States - Kitchens, Carl (Journal of Economic Literature, 2025)
Carl Kitchens of Florida State University reviews “Democracy in Power: A History of Electrification in the United States” by Sandeep Vaheesan. The Econlit abstract of this book begins: “Explores the history of public control of power systems in the United States, assessing how the United States has, at least partially, averted a net-zero oligarchy in power.”